Kajian yuridis pemberian insentif pajak penghasilan pada masa pandemi Covid-19 - Sariwati, Retno (Jurnal Cakrawala Hukum, 2021)
The President of the Republic of Indonesia has officially declared the Covid-19 pandemic a non-natural national disaster. This decision was stated by the President through Presidential Decree No. 12/2020. At the time of this pandemic, taxpayers have the right to get their rights because they have participated in this pandemic. contribute to the response to covid-19. The problem in this writing is how the juridical study of the collection of corporate income tax (PPh) for taxpayers during the Covid-19 pandemic. This writing uses a normative juridical method, and the result of the analysis of this problem is that the central government is more careful in making it easier for corporate taxpayers, especially those who have good intentions in contributing to the interests of overcoming the Covid-19 pandemic, namely by providing tax incentives where the tax incentive is in the form of a reduction in the amount income tax for corporate taxpayers. The principles in the national tax system must be represented in the form of government policies, that tax collection ultimately reflects the strengthening of national economic resilience and helps in accelerating national development, the Government can influence taxpayer compliance.How to cite item: Sariwati, R. (2021). Kajian yuridis pemberian insentif pajak penghasilan pada masa pandemi Covid-19. Jurnal Cakrawala Hukum, 12(1), 90-98.doi:10.26905/idjch.v12i1.5722.